Small Bowel Obstruction Secondary to a Metamucil Bezoar: Case Report and Review of the Literature - Sara Abou Azar; Mohammad Rachad Wehbe; Sarah Jamali; Ali Hallal (Case Reports in Surgery)
Bezoar-induced small bowel obstruction is a rare entity. It should be highly suspected in patients with gastric hypomotility disorders, psychiatric conditions, prior abdominal or bariatric surgery, or improper intake of medication. Their diagnosis is quite challenging and surgical exploration remains the best treatment of choice to ensure the viability of the small bowel tissue and relieve the obstruction. This is a case of a 48-year-old female with no previous abdominal surgery who presented with acute abdominal pain. The patient’s history was remarkable for the daily ingestion of 1.5 teaspoons of Metamucil with minimal amount of water. Computed tomography scan demonstrated dilated small bowel loops and a transition zone at the level of the mid jejunum. On laparoscopy, the patient was found to have a hard mass in the mid jejunum amenable to gentle fragmentation and breakdown. Metamucil bezoars are due to the solidification of psyllium-based substances in the gastrointestinal tract. The usual management of small bowel obstruction induced by a bezoar is exploratory laparotomy with enterotomy and primary anastomosis. Laparoscopic intervention has gained popularity among surgeons with good outcome and lower morbidity. In this unusual case, the small bowel obstruction induced by the Metamucil bezoar was safely treated with laparoscopic fragmentation alone.